Stillbirth memento photography. (2nd January 2020) - Tovey, Rob; Turner, Sarah
Abstract: Research into stillbirth memento photography shows the practice to be welcomed by the bereaved. The visual attributes and content of stillbirth memento photographs are yet to be rigorously analysed however, representing a significant gap in current understanding. This study seeks to address this. 51 professionally produced stillbirth memento photographs have been sampled, anonymised and analysed. Using a content analysis methodology, imagery was characterised by aesthetic and semantic properties. The results were then cross-referenced against existing stillbirth scholarship, data from an interview study with people who had experienced pregnancy loss, and against image theories. The content analysis identified four distinctive image tropes in the sample: images of mother, father and baby, with the baby being held and the parents touching; macro photography of the baby; portrait photographs of babies lying alone with little or no physical trauma evident; and images of a parent, usually the mother, cradling the baby. The analysis also identified specific attributes, present across the sample, that appeared significant and distinctive of stillbirth memento photography. These were: (1) stylistic attributes, (2) acknowledgement and validation, (3) identity construction, (4) ambiguity and (5) e mbodiment .